Food insecurity, food skills, health literacy and food preparation activities among young Canadian adults: a cross-sectional analysis. Issue 9 (2nd June 2021) - Pepetone, Alexandra; Vanderlee, Lana; White, Christine M; Hammond, David; Kirkpatrick, Sharon I
Abstract: Objective: To assess associations between household food security status and indicators of food skills, health literacy and home meal preparation, among young Canadian adults. Design: Cross-sectional data were analysed using logistic regression and general linear models to assess associations between food security status and food skills, health literacy and the proportion of meals prepared at home, by gender. Setting: Participants recruited from five Canadian cities (Vancouver (BC), Edmonton (AB), Toronto (ON), Montreal (QB) and Halifax (NS)) completed an online survey. Participants: 1389 men and 1340 women aged 16–30 years. Results: Self-reported food skills were not associated with food security status ( P > 0·05) among men or women. Compared to those with high health literacy (based on interpretation of a nutrition label), higher odds of food insecurity were observed among men (adjusted OR (AOR): 2·58, 95 % CI 1·74, 3·82 and 1·56, 95 % CI 1·07, 2·28) and women (AOR: 2·34, 95 % CI 1·48, 3·70 and 1·92, 95 % CI 1·34, 2·74) with lower health literacy. Women in food-insecure households reported preparing a lower proportion of breakfasts ( β = −0·051, 95 % CI −0·085, −0·017), lunches ( β = −0·062, 95 % CI −0·098, −0·026) and total meals at home ( β = −0·041, 95 % CI −0·065, −0·016). Men and women identifying as Black or Indigenous, reporting financial difficulty and with lower levels of education had heightened odds of experiencing food insecurity. Conclusions: Findings are consistent with other studies underscoring the financial precarity, rather than lack of food skills, associated with food insecurity. This precarity may reduce opportunities to apply health literacy and undertake meal preparation.